2021
DOI: 10.1371/journal.pone.0250165
|View full text |Cite
|
Sign up to set email alerts
|

Larazotide acetate induces recovery of ischemia-injured porcine jejunum via repair of tight junctions

Abstract: Intestinal ischemia results in mucosal injury, including paracellular barrier loss due to disruption of tight junctions. Larazotide acetate (LA), a small peptide studied in Phase III clinical trials for treatment of celiac disease, regulates tight junctions (TJs). We hypothesized that LA would dose-dependently hasten recovery of intestinal ischemic injury via modulation of TJs. Ischemia-injured tissue from 6-8-week-old pigs was recovered in Ussing chambers for 240-minutes in the presence of LA. LA (1 μM but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…For instance, Larazotide acetate is a small, TJ-directed drug that is currently in clinical trials for treatment of celiac disease, the pathophysiology of which includes disruptions to the intestinal TJs [130][131][132][133]. Several in vivo and in vitro experiments have demonstrated that Larazotide administration prevents relocalization of crucial TJ-proteins, ultimately resulting in quantifiably enhanced epithelial barrier integrity [134][135][136]. Taken together, these studies introduce the exciting prospect of compounding pre-and probiotic's beneficial effects with Larazotide or similar TJ-protein-directed pharmaceuticals.…”
Section: Future Directions: Embracing the Enteric Glial Cell Network Large Animal Models And Promising Clinical Interventionsmentioning
confidence: 99%
“…For instance, Larazotide acetate is a small, TJ-directed drug that is currently in clinical trials for treatment of celiac disease, the pathophysiology of which includes disruptions to the intestinal TJs [130][131][132][133]. Several in vivo and in vitro experiments have demonstrated that Larazotide administration prevents relocalization of crucial TJ-proteins, ultimately resulting in quantifiably enhanced epithelial barrier integrity [134][135][136]. Taken together, these studies introduce the exciting prospect of compounding pre-and probiotic's beneficial effects with Larazotide or similar TJ-protein-directed pharmaceuticals.…”
Section: Future Directions: Embracing the Enteric Glial Cell Network Large Animal Models And Promising Clinical Interventionsmentioning
confidence: 99%
“…It had been reported that 1 μM of AT1001 can blocked the ischemia-induced TJ dysfunction but higher concentration (10 μM) of AT1001 did not elicit better protective effects 32 , 33 . So, in preliminary experiments (n = 3 in each group), the dose-dependent effects of 5 μM, 10 μM, 20 μM of AT1001 for the inhibition of LPS-induced zonulin release in supernatant of Coca2 cells were tested.…”
Section: Methodsmentioning
confidence: 90%
“…Larazotide prevents TJ opening, being able to block zonulin receptors locally, by joining the receptors itself, decreasing TJ detachment and promoting TJ assembly and structural filaments rearrangement (288). Larazotide was developed for the treatment of CD (289) and later tested in type 1 diabetes, inflammatory bowel disease, Kawasaki disease, respiratory diseases (290), collagen-induced arthritis (291) and intestinal ischemic injury (292,293).…”
Section: Larazotidementioning
confidence: 99%